The Relationship between Hours of Work and Labor Force Participation in Four Models of Labor Supply Behavior - Zabel, Jeffrey E. (Journal of Labor Economics, 1993)
This article analyzes the relationship between hours of work and labor force participation (LFP) in Heckman's model, Cogan's fixed-cost model, Moffitt's minimum hours constraint model, and a generalized version of Heckman's model. First, the parameter restrictions between the LFP and reduced-form hours-of-work equations are compared. The models are then estimated, and the results support the weakening of the link between the LFP and hours-of-work decisions. One implication of the analysis is that Heckman's model overstates the standard labor supply elasticities because it confounds the direct effect on labor supply with the participation effect.